Examining Student ICT Ownership, Use and Preferences towards Electronically Delivered Learning Resources in Nakhon Phanom University and Sakon Nakhon Rajabhat University - Gulatee, Y.; Vonganusith, V.; Pagram, J.; Cooper, Martin (2016)
The objectives of this research were 1) to find students’ ownership of technology devices, ownership, software facility, and preferences, 2) to find out what devices instructors use in the classroom, 3) to fi nd out how the students use the online learning that the university provided for them, and 4) to examine students’ software skills. The questionnaire and the interview instruments were designed to clarify participants’ attitudes, and used a Likert scale. Surveys and qualitative research design were developed using Qualtrics software, which is an online research survey tool that can be used for a whole range of data gathering purposes applicable to Higher Degree Research. The samples are the students in both universities (Nakhon Phanom University and Sakon Nakhon Rajabhat University), a total of 977 people. A statistical computer program was employed. The entire reliability value was 0.852 and the discrimination index was between 0.28 and 0.76. The results disclose as follows: 1) Most of the students owned laptop (78%), followed by the smart phone (60%). The two university students owned devices up to 3 years, showed that students purchase new equipment all the time. Many students claimed that they used such devices in class (more than 60 %). As well as smart phones, students used them every day and more than 2-3 times (50 %). 2) The teachers used desktop computers, laptops and projectors in classrooms most frequently (> 75 %). 3) Only 20% of the students accessed communication channels provided by the universities, such as eLearning system, compared to other channels, such as Facebook. And 4) the students’ software skills required for studying are only at intermediate level, whereas their social media skills were advanced. As a result, it could be seen that most of the students lacked basic knowledge in using information technology for study purposes. Therefore, the university should have ongoing monitoring and measurement in respect of information technology competency as those technologies could constantly provide students with enthusiasm and give opportunity to improve themselves which is a good basis for future work and education.